Foliar spray of silica improved water stress tolerance in rice (Oryza sativa L.) cultivars - El-Okkiah, Samira A. F.; El-Afry, Mohamed M.; Shehab Eldeen, Safaa A.; El-Tahan, Amira M.; Ibrahim, Omar M.; Negm, Mostafa M.; Alnafissa, Mohamad; El-Saadony, Mohamed T.; Almazrouei, Hessa M. R. S.; AbuQamar, Synan F.; El-Tarabily, Khaled A.; Selim, Dalia A. (Frontiers in Plant Science, 2022)
Rice (Oryza sativa L.) is a major cereal crop and a staple food across the world, mainly in developing countries. Drought is one of the most important limiting factors for rice production, which negatively affects food security worldwide. Silica enhances antioxidant activity and reduces oxidative damage in plants. The current study evaluated the efficiency of foliar spray of silica in alleviating water stress of three rice cultivars (Giza178, Sakha102, and Sakha107). The seedlings of the three cultivars were foliar sprayed with 200 or 400 mg l-1 silica under well-watered [80% water holding capacity (WHC)] and drought-stressed (40% WHC)] conditions for two summer seasons of 2019 and 2020. The obtained results demonstrated that drought stress caused significant decreases in growth, yield, and physiological parameters but increases in biochemical parameters (except proline) of leaves in all rice cultivars compared to well-irrigated plants (control). The roots of drought-stressed seedlings exhibited smaller diameters, fewer numbers, and narrower areas of xylem vessels compared to those well-watered. Regardless of its concentration, the application of silica was found to increase the contents of photosynthetic pigments and proline. Water relation also increased in seedlings of the three tested rice cultivars that were treated with silica in comparison to their corresponding control cultivars when no silica was sprayed. Foliar application of 400 mg l-1 silica improved the physiological and biochemical parameters and plant growth. Overall, foliar application of silica proved to be beneficial for mitigating drought stress in the tested rice cultivars, among which Giza178 was the most drought-tolerant cultivar. The integration of silica in breeding programs is recommended to improve the quality of yield and to provide drought-tolerant rice cultivars under drought-stress conditions.